Pengaruh Literasi Keuangan Mahasiswa Terhadap Keputusan Investasi di Pasar Modal Studi pada Mahasiswa Indonesia dan Mahasiswa di Negara Potensial. - Mutia Ulfa; Ahmad Aufar Ribhi; Nita Ilmiyatul Lailiyah; Vincensia Serenade; Imam Syafii (STIE Amkop Makassar, 2023)
Financial literacy is knowledge about finance and its management. One of the knowledge in financial literacy is related to investing in the capital market. Investment itself is an activity that consciously and consistently invests the money you have to get more returns in the future. Investment decisions must be taken appropriately so that there is no risk of loss later. This research is a literature study, with data collection methods that use the identification, evaluation, interpretation, and search of literature sourced from accredited national and international journals. The journals used in this study totaled 14 articles published in 2019-2023 obtained from the Google Scholar, Crossref, and IEEE websites. The results of observations of several journals used, state that financial literacy has a significant and positive influence on investment decisions, which means changes in the value of financial literacy will affect changes in the value of student investment decisions.